(untitled) (Economic studies journal, 2020)
Forecasting is an important tool for decision making. It is utilized, In particular, by stakeholders such as dealers and risk managers to decide about the potential exchange rate transactions. Our aim is to forecast the behavior of Dollar/LD foreign exchange rate in a predetermined target horizon using Monte Carlo simulation. Modeling procedures are focused mainly on Brownian motion. Inferences about mean exchange rate and value-at-risk at the target horizon are also considered.